Anthocyanidin nanoparticles and preparation method thereof

The nanoparticles were prepared by lactoferrin and sodium carboxymethylcellulose to wrap anthocyanins, which solved the problem of poor stability of anthocyanins, achieved the improvement of its thermal, light and storage stability, and improved its application value in the food industry.

CN119699570AActive Publication Date: 2025-03-28CHENGDU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411911486.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Due to its structural characteristics and poor stability, anthocyanins are susceptible to environmental factors to cause oxidative discoloration and reduced biological activity, which limits their application in the food industry.

Method used

By encapsulating lactoferrin and sodium carboxymethylcellulose into anthocyanins, nanoparticles are prepared, and the electrostatic interaction is used to form stable nanocomplexes to improve the stability of anthocyanins.

Benefits of technology

The thermal stability, photostability and storage stability of anthocyanins have been greatly improved, the reaction between anthocyanins and environmental factors has been reduced, and its application value as a food additive has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119699570A_ABST
    Figure CN119699570A_ABST
Patent Text Reader

Abstract

The invention provides an anthocyanin nano-particle which is prepared by wrapping anthocyanin with lactoferrin and sodium carboxymethyl cellulose, and the weight ratio of the lactoferrin to the sodium carboxymethyl cellulose to the anthocyanin is as follows: 12.8 to 19.2 parts of the lactoferrin, 2.56 to 3.84 parts of the sodium carboxymethyl cellulose and 12.8 to 19.2 parts of the anthocyanin. The invention also provides a preparation method and application of the anthocyanin nanoparticles. In order to avoid structural change of anthocyanin in the preparation process, a green and safe self-assembly method is adopted, and synthesis conditions are adjusted on the premise that no chemical coupling agent or chemical emulsifier is added. The invention provides a simple, safe and environment-friendly synthesis method, provides an anthocyanin nutrition additive with more stable properties and safe components for the market, and provides an onset basis and technical support for developing foods and beverages containing stable anthocyanin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to anthocyanin nanoparticles and a preparation method thereof. Background Art

[0002] Anthocyanin (ACN) is a water-soluble flavonoid pigment, often used as a food coloring or nutritional additive in the food industry. It is reported to have a variety of biological activities, including antioxidant, anti-inflammatory and anti-cancer. However, due to its electron-deficient structural characteristics, it is extremely vulnerable to attack by reactive oxygen anions and free electrons, resulting in poor stability and easy degradation of anthocyanins. Changes in pH value, light, heating, enzyme effects, oxygen and metal ion contact during processing, storage or cooking can lead to oxidative discoloration and reduced biological activity of anthocyanins, which greatly limits the commercial application of anthocyanins as natural pigments and nutritional additives.

[0003] At present, there are many research papers on the stability of anthocyanins, such as: converting anthocyanins into acylated anthocyanins through chemical reactions to improve their stability. For example, using succinic acid, methyl salicylate, methyl benzoate, etc. as acyl donors to prepare acylated anthocyanins under the catalysis of biological complex enzymes can greatly improve the thermal stability, light stability, and heavy metal ion resistance of anthocyanins (patent application number: CN202111352413.2, invention name: A biological enzyme complex and a method for its application in plant extraction). However, since the solvent of the acylation reaction is mostly a mixture solution of multiple organic reagents, the anthocyanin sample stabilized by acylation must be completely detoxified or proved to be safe for consumption before being applied to food, and cannot be directly used for food addition; Patent application number: 202210609647.9, invention name: A method for improving the stability of anthocyanins, discloses a method for improving the stability of anthocyanins using peach gum polysaccharide, comprising the following steps: washing the peach gum and drying it to constant weight and crushing it, using distilled water as a solvent, fully swelling the peach gum, adding a certain amount of sodium hydroxide to hydrolyze it, adjusting its pH to neutral, concentrating it, and adding ethanol to fully precipitate the peach gum polysaccharide. Then, the peach gum polysaccharide and anthocyanin are fully mechanically mixed to obtain a peach gum polysaccharide-anthocyanin complex. The solubility, anti-heavy metal ion stability, thermal stability, and alkali stability of the complex were then measured. Due to the encapsulation of anthocyanins by peach gum polysaccharides in the mixture, the short-term dissolution rate of the complex (within 120 min) is significantly improved compared with anthocyanins, but the composite strength of the two is not high, and the storage stability needs to be improved. Xu Qing, et al., Research Progress on Factors Affecting the Stability of Anthocyanins and Improvement Methods, Food Research and Development, April 2020, Vol. 41, No. 7, Anthocyanins can form complexes with organic macromolecules such as proteins, cyclodextrins, and polysaccharides through interactions such as hydrogen bonds, electrostatic effects, and hydrophobic effects, thereby improving their thermal stability and storage stability. Therefore, it is feasible to use macromolecules such as proteins to self-assemble with anthocyanins to form complexes, but currently most of them are binary complexes formed by anthocyanins with single macromolecules, and research on ternary complexes is relatively lacking. Wu's study found that mannoprotein can form a complex with anthocyanins through hydrophobic interactions, which increases the thermal stability of anthocyanins (pH 7.0, heat treatment at 80°C or 126°C for 30 min) by 4 to 5 times. However, mannoprotein itself is prone to aggregation, the average size of its synthesized complex is 279.4nm, and it has significant thermal aggregation behavior when heated, which is not conducive to the anthocyanin nanoparticles maintaining stable properties during high-temperature processing.

[0004] At present, most of the literature on the stability of anthocyanins is about extracting anthocyanins from plants, and there are fewer literatures on changing the stability through preparations. The latest developments in nanotechnology have provided some feasible methods for the preparation of anthocyanin nanoformulations, such as improving the physicochemical stability, bioavailability and biological activity by actively or passively combining with macromolecular substances. Embedding anthocyanins into the structure of nanoparticles can separate them from the external environment to a certain extent, reduce the reaction of anthocyanins with environmental factors, and achieve the effect of stabilizing anthocyanins. The functional properties of nanoparticles such as size, encapsulation efficiency and stability are affected by the type of wall material and the synthesis method. At present, there are no literature reports that anthocyanin nanoparticles can not only solve the stability of anthocyanins, but also achieve a high encapsulation rate. Summary of the invention

[0005] The present invention provides anthocyanin nanoparticles and a preparation method of the anthocyanin nanoparticles.

[0006] The present invention provides anthocyanin nanoparticles, which are prepared by encapsulating anthocyanin with lactoferrin and sodium carboxymethyl cellulose to form nanoparticles, wherein the weight ratio of lactoferrin, sodium carboxymethyl cellulose and anthocyanin is:

[0007] Lactoferrin 12.8-19.2 parts, sodium carboxymethyl cellulose 2.56-3.84 parts, anthocyanin 12.8-19.2 parts.

[0008] Further preferably, the weight ratio of lactoferrin, sodium carboxymethyl cellulose and anthocyanin is:

[0009] 16 parts of lactoferrin, 3.2 parts of sodium carboxymethyl cellulose, and 16 parts of anthocyanins.

[0010] Wherein, the degree of substitution DS of the sodium carboxymethyl cellulose is 0.7-1.2. More preferably, the degree of substitution DS of the sodium carboxymethyl cellulose is 0.9.

[0011] The anthocyanin nanoparticles of the present invention are prepared by adding anthocyanin into a sodium carboxymethylcellulose dispersion solution, stirring, then adding a lactoferrin solution, and stirring to obtain the anthocyanin nanoparticles.

[0012] The present invention provides a method for preparing anthocyanin nanoparticles, which comprises the following steps:

[0013] a. Dissolve anthocyanin in 0.2M pH 3.0 citric acid buffer, place on a magnetic stirrer and stir continuously for 1 hour at room temperature. Store the obtained anthocyanin solution away from light;

[0014] b. preparing aqueous solutions of lactoferrin and sodium carboxymethyl cellulose respectively, stirring them magnetically at 75° C. and 40° C. for 1 hour respectively, and then adjusting the pH value to 5.0 with dilute hydrochloric acid;

[0015] c. Take the sodium carboxymethyl cellulose dispersion solution into a brown bottle with a lid and keep stirring it at a constant speed on a magnetic stirrer; use a syringe to sample the anthocyanin solution in step a, add it dropwise into the bottle, stir for 30 minutes to ensure uniform mixing, and then adjust the pH value to 5.0;

[0016] d. Take the lactoferrin solution, add it dropwise into the bottle, and stir it continuously on a magnetic stirrer for 24 hours to obtain a nanoparticle mixed solution;

[0017] e. Filtration: The mixed solution in step d is filtered through an ultracentrifugal filter with a nominal molecular weight limit of 30 kDa at 1000×g for 20 min to remove the unencapsulated free anthocyanins; then filtered through a filter membrane with a pore size of 0.45 μm to remove impurities, thereby obtaining anthocyanin nanoparticle dispersion.

[0018] Lactoferrin (LF) used in the present invention is a natural protein in milk. As a glycoprotein of the transferrin family, it is a good and safe drug nanocarrier and is also commonly used in the food field to prepare nanoparticles of bioactive small molecules. When nanoparticles are prepared by a gentle method based on lactoferrin, relatively safe products can usually be obtained without involving any chemical reaction. It is worth noting that the isoelectric point (pI≈8.5) of lactoferrin is higher than that of most other proteins (pI≈5). When coexisting in an aqueous solution with other negatively charged macromolecular substances, nanocomposites can be formed under electrostatic interaction. Sodium carboxymethylcellulose (CMC) is usually an anionic polymer compound prepared by reacting natural cellulose with caustic soda and monochloroacetic acid. It can form a polymer with excellent encapsulation ability when combined with other biological substances, so it is also a good nanoparticle wall material.

[0019] The present invention selects lactoferrin and sodium carboxymethyl cellulose to combine under mild reaction conditions, and anthocyanin is embedded under the electrostatic attraction of negatively charged sodium carboxymethyl cellulose and positively charged lactoferrin molecules to form stable nanoparticles. Reaction conditions such as reaction pH, sodium carboxymethyl cellulose substitution degree, raw material loading sequence, sodium carboxymethyl cellulose treatment temperature, and lactoferrin treatment temperature are investigated and optimized to obtain smaller and more stable anthocyanin nanoparticles, and the microscopic morphology, infrared spectrum information and stability of the anthocyanin nanoparticles are characterized.

[0020] In order to avoid structural changes of anthocyanidins during the preparation process, the present invention adopts a green and safe self-assembly method, and adjusts the synthesis conditions without adding any chemical coupling agents and chemical emulsifiers. The present invention is a simple, safe and environmentally friendly synthesis method, which provides the market with a more stable and safe anthocyanidin nutritional additive, and provides a theoretical basis and technical support for the development of food and beverages containing stable anthocyanidins. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Process flow chart of the sample preparation process of anthocyanin nanoparticle dispersion coated with lactoferrin and sodium carboxymethylcellulose;

[0022] Figure 2 ζ-potential values ​​of lactoferrin (LF) and sodium carboxymethyl cellulose (CMC) at different pH and the SEI value between them;

[0023] Figure 3 Fourier transform infrared spectra of raw materials and nanoparticle samples prepared according to the method;

[0024] Figure 4 Scanning electron microscope images of blank nanoparticles (left) and nanoparticle samples prepared according to the present method (right);

[0025] Figure 5 Nanoparticle stability test results (A) Particle size change trend after heating in a water bath at 90°C for 3 hours, (B) Particle size change trend after dilution at different times, (C) Particle size change trend after continuous storage for 15 days;

[0026] Figure 6 Results of anthocyanin retention stability experiment (A) The trend of anthocyanin retention rate under different pH, (B) The trend of anthocyanin retention rate over time when stored in a 4℃ light environment, (C) The trend of anthocyanin retention rate over time when stored in a 4℃ dark environment, (E) The trend of anthocyanin retention rate over time when stored in a 25℃ dark environment. DETAILED DESCRIPTION

[0027] Example 1 Preparation method of anthocyanin nanoparticles of the present invention

[0028] The preparation process of anthocyanin nanoparticles coated with lactoferrin and sodium carboxymethylcellulose is described as follows Figure 1As shown. Anthocyanins were dissolved in 0.2M pH 3.0 citric acid buffer, placed on a magnetic stirrer and stirred continuously for 1h at room temperature to obtain a 4mg / mL anthocyanin solution, which was stored at 4°C in the dark until use. 1.6mg / mL lactoferrin LF and 0.32mg / mL sodium carboxymethyl cellulose CMC aqueous solutions were prepared. After magnetic stirring for 1 hour at 75°C and 40°C, respectively, the pH values ​​of the LF and CMC dispersion solutions were immediately adjusted to 5.0 with dilute hydrochloric acid. To avoid oxidative decomposition of anthocyanin samples during the preparation process, the dispersion of the packaging material should be cooled to room temperature before adding anthocyanins, and protected from light throughout the process. Take 10mL of CMC dispersion solution in a brown bottle with a cap and keep stirring at a constant speed on a magnetic stirrer. Use a syringe to accurately sample 4mL of anthocyanin solution, add it dropwise to the bottle, cover the bottle cap, and stir continuously for 30min to allow the solution to fully mix and react. Subsequently, the pH value of the reaction system was adjusted to 5.0 with sodium hydroxide solution to achieve the optimal reaction conditions for LF. After that, 10 mL of LF solution was accurately sampled with a syringe, added dropwise to the bottle, capped, and stirred continuously on a magnetic stirrer for 24 h to obtain a nanoparticle mixed solution. The free anthocyanins that were not embedded in the mixed sample could be removed by ultrafiltration at 1000 × g for 20 min using an ultracentrifugal filter with a nominal molecular weight limit of 30 kDa, while the larger impurity particles were removed by filtration with a filter membrane with a pore size of 0.45 μm. The final sample was a nanoparticle dispersion, which was stored at 4 ° C in the dark for further study.

[0029] Example 2 Process Investigation Test of the Preparation Method of Anthocyanin Nanoparticles of the Present Invention

[0030] Before optimizing the synthesis process, the preparation process of anthocyanin nanoparticles encapsulated by lactoferrin and sodium carboxymethylcellulose is briefly described as follows:

[0031] Take 10mL of CMC dispersion solution in a brown bottle with a lid and keep stirring at a constant speed on a magnetic stirrer. Use a syringe to accurately sample 10mL of LF solution, add it dropwise to the bottle, cover the bottle cap, and stir continuously for 1h to allow the solution to mix and react. Subsequently, cool at room temperature for 30min to avoid thermal decomposition of subsequent anthocyanins added to the system. After that, use a syringe to accurately sample 4mL of anthocyanin solution, add it dropwise to the bottle, cover the bottle cap, stir continuously at room temperature for 30min, and adjust the pH value of the reaction system to 5.0 with sodium hydroxide solution to achieve the optimal reaction conditions for LF, and continue to stir continuously on the magnetic stirrer for 24h to obtain a nanoparticle mixed solution. The free anthocyanins that were not embedded in the mixed sample were removed by ultrafiltration at 2700×g for 20 min using an ultracentrifugal filter with a nominal molecular weight limit of 30 kDa, while the larger impurity particles were removed by filtration through a filter membrane with a pore size of 0.45 μm. The final sample was the nanoparticle dispersion, which was stored at 4°C in the dark for further study.

[0032] 1. Choice of reaction pH

[0033] like Figure 2 As shown in the middle line graph, the ζ-potential of lactoferrin and sodium carboxymethyl cellulose in aqueous solutions with different pH values ​​was measured, and the concept of electrostatic interaction intensity (SEI value) was introduced to provide a more intuitive method to quantify the electrostatic force between lactoferrin and sodium carboxymethyl cellulose. Among them, lactoferrin and sodium carboxymethyl cellulose were both 1 mg / mL aqueous solutions. According to the nanoparticle preparation process, they were heated and stirred at 75°C and 40°C, and the pH was adjusted to 3, 4, 5, 6, and 7. The SEI value is calculated based on the ζ-potential of lactoferrin and sodium carboxymethyl cellulose with different degrees of substitution (DS) at the same pH, and its value is the product of the absolute values ​​of the two.

[0034] In the pH range studied, the ζ-potential of lactoferrin gradually decreased from 37.77±1.44mV to 16.80±1.18mV as the solution became more alkaline, however, it always showed positive electrical properties. Sodium carboxymethylcellulose is negatively charged over a wide pH range, and the ζ-potentials of sodium carboxymethylcellulose with different degrees of substitution vary slightly. The degree of substitution is directly related to the number of charged groups attached to the sodium carboxymethylcellulose molecule, which increases the charge density of the polysaccharide, which in turn causes polysaccharides with higher degrees of substitution to show stronger charge properties in aqueous solution.

[0035] Affected by the low charge density of sodium carboxymethyl cellulose, under acidic conditions, especially when the pH value is close to 3, the SEI value drops to its lowest point (about 285.02 to 448.07 mV 2). At neutral pH, pH 7, lactoferrin is close to the isoelectric point, and the net charge gradually approaches zero, which will also reduce the SEI value. Therefore, when selecting a reaction system, a moderate pH value can improve the charging properties of proteins and polysaccharides. In this experiment, the electrostatic interaction strength between lactoferrin and three different DS sodium carboxymethyl celluloses reached a peak at pH 5, which is considered to be the ideal reaction condition for CMC to form nanocomplexes with LF.

[0036] 2. Selection of sodium carboxymethyl cellulose with different degrees of substitution

[0037] Three kinds of sodium carboxymethyl cellulose were used as raw materials to prepare nanoparticles according to the above process flow. The average particle size and polydispersity index (PDI) were determined by dynamic light scattering (DLS), the ζ-potential was determined by electrophoresis, and the anthocyanin content was determined by HPLC-DAD to calculate the anthocyanin encapsulation efficiency. The results are shown in Table 1.

[0038] Table 1 Performance indicators of nanoparticles prepared from sodium carboxymethyl cellulose with different degrees of substitution

[0039]

[0040] Different letters in the same column indicate significant differences (P<0.05)

[0041] It can be inferred that sodium carboxymethyl cellulose with a higher degree of substitution will produce more electrostatic repulsion between CMC molecular chains, thereby inhibiting the formation of nanoparticles of uniform size. However, due to the higher charge density, sodium carboxymethyl cellulose with DS=1.2 can improve the particle properties of nanoparticles and obtain smaller and more stable nanoparticles. However, due to the stronger hydrophilicity of anthocyanins, the larger specific surface area increases the probability of free anthocyanins in the particles to escape. Therefore, the encapsulation effect of nanoparticles prepared with sodium carboxymethyl cellulose with DS=1.2 is not ideal. As the particle size of NPs increases, the specific surface area in the solution decreases, which is also not conducive to the adsorption of anthocyanins. Therefore, the anthocyanin encapsulation efficiency of sodium carboxymethyl cellulose with DS=0.7 is also low. In addition, its average particle size and PDI are slightly larger, and the structure of the particles is relatively loose, which cannot tightly and stably fix small molecules in the particles. Medium DS values ​​can provide higher anthocyanin encapsulation efficiency, and the sample has good particle properties. In summary, sodium carboxymethyl cellulose with DS=0.9 is more suitable for the preparation of nanoparticles.

[0042] 3. Selection of loading order for different raw materials

[0043] In the experiment, four sequences were also selected to prepare different nanoparticle samples according to the above established experimental conditions. The abbreviation order in the sample name represents the loading order. In order to reflect the influence of different addition sequences on the loading effect of anthocyanin (ACN), we set two ultrafiltration conditions of 1000×g and 2700×g for comparison. The performance indicators of the obtained nanoparticles are shown in Table 2.

[0044] Table 2 Performance indicators of nanoparticles prepared under different raw material loading sequences

[0045]

[0046] Different letters in the same column indicate significant differences (P<0.05)

[0047] The addition of ACN, LF and CMC sequences can directly affect the interaction of these materials, thereby affecting the structural properties of the nanocomplexes. In the samples of group A, the oppositely charged sodium carboxymethyl cellulose and lactoferrin were initially electrostatically bound to form larger particles. When the CMC-LF complex was formed, anthocyanins could not overcome the electrostatic repulsion with lactoferrin on the particle surface and could only be adsorbed on the CMC molecular branches to a limited extent, resulting in a low encapsulation efficiency of the samples. When a large mechanical force was used to remove the small molecule particles in the dispersion, the particle size of the samples of group A decreased, and at the same time, the anthocyanin encapsulation efficiency decreased to 65.73%. These changes can be attributed to the separation of anthocyanin molecules adsorbed on the outer surface of the particles under strong forces. In contrast, the loading sequence of group B was more scientific and reasonable. The positively charged anthocyanins and the negatively charged sodium carboxymethyl cellulose reacted with each other first, allowing the nanoparticles to encapsulate more anthocyanin molecules in the center of the structure, resulting in the maximum anthocyanin encapsulation efficiency. After the outer layer is covered with positively charged protein, a relatively compact particle structure is formed, which can resist changes caused by strong external forces. Therefore, when the centrifugal force is increased, the particle size will not change significantly. For the samples in group C, both protein and anthocyanin are positively charged and are evenly dispersed in the aqueous solution by electrostatic repulsion. Even if sodium carboxymethyl cellulose is added, it is difficult to form particles of uniform size. Therefore, the PDI value of the obtained product is the largest and the encapsulation efficiency is the smallest. The particle size results of group D are equivalent to those of group A, which is also not conducive to the formation of stable nanoparticles. In summary, the loading order of dripping anthocyanin into sodium carboxymethyl cellulose for reaction and then adding lactoferrin is more conducive to the formation of nanoparticles. At the same time, the centrifugal force of ultrafiltration is adjusted to 1000×g to reduce the consumption of anthocyanin during sample preparation.

[0048] 3. Selection of treatment temperature of sodium carboxymethyl cellulose

[0049] Four points between room temperature and 80°C were selected as investigation factors, and the performance indicators of the prepared nanoparticles are shown in Table 3.

[0050] Table 3 Performance indicators of nanoparticles prepared by sodium carboxymethyl cellulose treated at different temperatures

[0051]

[0052] Different letters in the same column indicate significant differences (P<0.05)

[0053] Appropriate heating can enhance the charge of sodium carboxymethyl cellulose, but when the temperature reaches 80°C, the charge decreases. In general, the critical temperature of CMC is between 80°C and 100°C. If the temperature exceeds this range, the adhesion and solubility of CMC will drop sharply, or even fail completely. Therefore, the ζ-potential of the prepared nanoparticles is also affected, and the absolute value of the charge shows a trend of first increasing and then decreasing. However, the change in the treatment temperature of sodium carboxymethyl cellulose has no effect on the encapsulation efficiency of anthocyanins, and there is no significant difference between the groups. It can be seen that heating does not change its binding strength on anthocyanins and lactoferrin. Therefore, in the subsequent process, we chose 40°C as the treatment temperature of sodium carboxymethyl cellulose to obtain smaller nanoparticles with less energy consumption.

[0054] As for the selection of the treatment temperature of lactoferrin, since the two denaturation temperatures of bovine lactoferrin under neutral pH conditions are 60.4°C (for N leaf) and 89.1°C (for C leaf), we selected four temperature gradients of 45°C, 60°C (near the denaturation temperature of N leaf), 75°C, and 90°C (near the denaturation temperature of C leaf) to treat LF, and the particle size results and anthocyanin encapsulation efficiency of the obtained samples are shown in Table 4.

[0055] Table 4 Performance indicators of nanoparticles prepared from lactoferrin treated at different temperatures

[0056]

[0057] Different letters in the same column indicate significant differences (P<0.05)

[0058] Under the influence of the two denaturation temperatures of lactoferrin, the nanoparticle dispersion system has the largest particle size (246.3±4.3nm) near its first denaturation temperature of 60℃, followed by the second denaturation temperature of 90℃ (176.3±1.1nm). At this time, the N and C leaves are unfolding, and the chaotic and relatively stretched protein conformation is not conducive to the formation of nanoparticles. Therefore, the encapsulation efficiency of anthocyanins at these two temperatures is also significantly lower. The absolute value of the potential of the nanoparticle sample obtained under 45℃ treatment is too low, and the PDI is slightly higher, so it is also not considered. At 75℃, between the two denaturation temperatures, a relatively stable and uniform nanoparticle dispersion system can be formed with a higher encapsulation efficiency. Therefore, the final selected LF treatment temperature is 75℃.

[0059] Example 3 Characterization experiment of anthocyanin nanoparticles of the present invention

[0060] Anthocyanin nanoparticle samples coated with lactoferrin and sodium carboxymethyl cellulose were prepared according to the optimized process flow, and the infrared spectrum and microscopic morphology of the final product were characterized to determine whether nanoparticles were formed.

[0061] Figure 3 The following are Fourier transform infrared spectra of lactoferrin (LF), sodium carboxymethyl cellulose (CMC), anthocyanin (ACN), blank nanoparticles (CMC+LF) and nanoparticle samples (NPs) prepared according to the method. For lactoferrin, the amide A band (3500-3200cm -1 ) is identified at 3302cm -1 , while the amide I band (1625-1750cm -1 ), amide II band (1475-1575cm -1 ), amide III band (1225-1425cm -1 ) peaks at 1655, 1536, and 1391 cm -1 Compared with LF, the amide A band of the nanoparticle sample was significantly red-shifted, the amide I band and amide III band were displaced, and the characteristic peak of the amide II band disappeared, which indicated that the amide bond conformation and intramolecular hydrogen bond of LF changed after the formation of nanoparticles. When CMC formed a conjugate with LF, the OH stretching vibration of sodium carboxymethyl cellulose changed from 3426cm -1 Transfer to 3414cm -1 , revealing the generation of hydrogen bonds between the two. In addition, at 1628 cm -1 The carboxyl absorption peak at 1438 cm -1 The buckling signal at 1283 cm is masked by the influence of the LF signal, which also confirms the existence of electrostatics in contact. -1 The typical absorption band of flavonoids at 1343 cm -1 The absorption band at corresponds to the CO angle deformation of phenol. After anthocyanin is encapsulated into nanoparticles, these two characteristic peaks weaken or even disappear, which indicates that anthocyanin is successfully encapsulated by nanoparticles and is successfully embedded inside the particles.

[0062] The microstructure and dispersion of nanoparticles Figure 4The SEM images in the figure show that sodium carboxymethyl cellulose has a chain structure and will become "spongy" after freeze-drying and dehydration. Therefore, when the blank nanoparticle sample of CMC+LF is observed under a scanning electron microscope, the fiber structure of sodium carboxymethyl cellulose forms a complex three-dimensional electrostatic entanglement structure with lactoferrin and shows a larger microscopic size. When an excess of anthocyanin is added to the reaction system, it causes a strong interference to the electrostatic complexation between sodium carboxymethyl cellulose and lactoferrin. This effect causes the network structure of the LF+CMC complex to unravel, forming small, dense and relatively dispersed nanoparticles. From the scanning electron microscope image, the microscopic morphology of the nanoparticles prepared according to this method is close to spherical, with a smooth and uniform surface and no visible pores or cracks, indicating that these particles have a certain rigid structure.

[0063] Example 4 Stability test of nanoparticles prepared by the present invention

[0064] Particle stability of nanoparticles Figure 5 Indicates. Figure 5 In (A), the average particle size of the nanoparticles increased significantly after high-temperature treatment at 90°C, but the particle size was able to remain smaller within a certain range and remain dynamically stable during long-term heating. After continuous heating for 3 hours, the particle size of the sample had recovered, indicating that the nanoparticle sample had good thermal stability after high-temperature treatment at 90°C. Figure 5 In (B), at a dilution concentration of less than 20 times, the nanoparticles can maintain a certain size of particle size stability. However, when the dilution factor increases to a certain extent, the increase in the particle size of the complex is related to the weakening of the interaction between the components at low concentrations, so the particle size increases sharply. This shows that the nanoparticles have good dilution stability within a 20-fold dilution volume. Figure 5 As can be seen in (C), within 9 days of the test period, the nanoparticles were able to maintain a relatively stable particle size and dispersion, and from 12 days onwards, a significant size increase was observed. Despite the increase in particle size, the nanoparticles still showed a good size of 218.8 nm on the 15th day, indicating that the nanoparticles had good storage stability during the analysis period.

[0065] Figure 6 The effects of pH, light, and temperature on anthocyanin retention were evaluated to understand the environmental limits of the nanoparticles’ useful applications. Figure 6 (A) It can be seen that pH has a great influence on the stability of anthocyanins, and in the wide range of pH 3-8, nanoparticles always have a positive effect on the retention rate of anthocyanins. Figure 6(B) It can be seen that the retention rate of anthocyanins in nanoparticles and free anthocyanins decreases over time under light conditions, but the retention rate of anthocyanins in nanoparticle samples is always higher than that in free anthocyanin samples. Therefore, the formation of nanoparticles has a certain light protection effect on anthocyanins. Storage temperature has a significant effect on the stability of anthocyanins. Figure 6 (C) Figure 6 (D) is the anthocyanin retention rate of the two samples stored at 4°C and 25°C, respectively. After 20 days, at 4°C and 25°C, the retention rate of anthocyanin in the nanoparticles remained above 90.4% and 72.7%, respectively, reflecting that the electrostatic interaction between the core and wall materials stabilizes the composite structure and can effectively protect anthocyanin. Overall, the anthocyanin retention rate of the nanoparticle sample is always higher than that of the free anthocyanin sample, which shows that the nanocarrier prepared by this method can indeed reduce the degradation of anthocyanin by environmental factors.

Claims

1. Anthocyanin nanoparticles, characterized in that: The method comprises encapsulating anthocyanin with lactoferrin and sodium carboxymethyl cellulose to prepare nanoparticles, wherein the weight ratio of lactoferrin, sodium carboxymethyl cellulose and anthocyanin is: Lactoferrin 12.8-19.2 parts, sodium carboxymethyl cellulose 2.56-3.84 parts, anthocyanin 12.8-19.2 parts.

2. The anthocyanin nanoparticles according to claim 1, characterized in that: The weight ratio of lactoferrin, sodium carboxymethyl cellulose and anthocyanin is: 16 parts of lactoferrin, 3.2 parts of sodium carboxymethyl cellulose, and 16 parts of anthocyanins.

3. The anthocyanin nanoparticles according to claim 1 or 2, characterized in that: The degree of substitution DS of the sodium carboxymethyl cellulose is 0.7-1.

2.

4. The anthocyanin nanoparticles according to claim 3, characterized in that: The degree of substitution DS of the sodium carboxymethyl cellulose is 0.

9.

5. The anthocyanin nanoparticles according to any one of claims 1 to 4, characterized in that: The method comprises the steps of adding anthocyanin into a sodium carboxymethyl cellulose dispersion solution, stirring the solution, and then adding a lactoferrin solution, and stirring the solution to obtain anthocyanin nanoparticles.

6. A method for preparing anthocyanin nanoparticles according to any one of claims 1 to 4, characterized in that: It includes the following steps: a. Dissolve anthocyanin in 0.2M pH 3.0 citric acid buffer, place on a magnetic stirrer and stir continuously for 1 hour at room temperature. Store the obtained anthocyanin solution away from light; b. preparing aqueous solutions of lactoferrin and sodium carboxymethyl cellulose respectively, stirring them magnetically at 75° C. and 40° C. for 1 hour respectively, and then adjusting the pH value to 5.0 with dilute hydrochloric acid; c. Take the sodium carboxymethyl cellulose dispersion solution into a brown bottle with a lid and keep stirring it at a constant speed on a magnetic stirrer; use a syringe to sample the anthocyanin solution in step a, add it dropwise into the bottle, stir for 30 minutes to ensure uniform mixing, and then adjust the pH value to 5.0; d. Take the lactoferrin solution, add it dropwise into the bottle, and stir it continuously on a magnetic stirrer for 24 hours to obtain a nanoparticle mixed solution; e. Filtration: The mixed solution in step d is filtered through an ultracentrifugal filter with a nominal molecular weight limit of 30 kDa at 1000×g for 20 min to remove the unencapsulated free anthocyanins; then filtered through a filter membrane with a pore size of 0.45 μm to remove impurities, thereby obtaining anthocyanin nanoparticle dispersion.

Citation Information

Patent Citations

  • Bio-enzyme compound and method for applying bio-enzyme compound to plant extraction process

    CN113980485A

  • A method for improving the stability of anthocyanins

    CN114957185B

  • Anthocyanin nano-composite with core-shell structure and preparation method thereof

    CN109222069A

  • Method for preparing astaxanthin / DNA / lactoferrin nanoparticles and application of astaxanthin / DNA / lactoferrin nanoparticles

    CN115868637A

  • Method for improving stability and steady-state embedding of anthocyanin

    CN118452456A